Carpal Tunnel Syndrome: Causes, Prevention, Rehabilitation and Computer-Aided, Game-Based Physiotherapy - Tsilidi, Diana; Pachoulakis, Ioannis; Analyti, Anastasia (European Journal of Applied Sciences, 2018)
Carpal Tunnel Syndrome (CTS) is caused by improper computer posture and usage of the arms and hands. It expresses a conglomerate of symptoms caused by the compression of the median nerve as it passes through the carpal tunnel of the wrist. These include pain, numbness and tingling in affected parts of the hand. CTS treatment may take the form of surgery and/or physiotherapy. This paper revisits the causes of CTS and the common prevention tactics and focuses on the emerging role of rehabilitation via computer-aided, game-based physiotherapy which can augment a more traditional exercise curriculum.